1989
DOI: 10.1073/pnas.86.23.9519
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin's amino-terminal cleavage peptide is a bone-cell mitogen.

Abstract: The parafollicular-cell (C-cell) hormone calcitonin (CT) can preserve or even augment skeletal mass by inhibiting osteoclast-mediated bone resorption. The possibility of an additional anabolic skeletal influence has also been raised: C cells might, via CT or other secretory products, affect osteoblast-mediated bone formation. The 57-residue aminoterminal procalcitonin cleavage peptide, N-proCT, has recently been identified in human and rat C cells, where it is made and secreted in equimolar amounts with CT. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…It has been reported that circulating levels of PCT and N-PCT are dramatically elevated in severe infections, and that PCT-messenger RNA is ubiquitously and uniformly expressed in multiple tissues throughout the body in response to sepsis [14,15,16,17,18,19,20]. However, in contrast to N-PCT, PCT by itself has no known biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that circulating levels of PCT and N-PCT are dramatically elevated in severe infections, and that PCT-messenger RNA is ubiquitously and uniformly expressed in multiple tissues throughout the body in response to sepsis [14,15,16,17,18,19,20]. However, in contrast to N-PCT, PCT by itself has no known biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies focused on the inhibition of bone resorption by CGRPα, although effects were seen only at supraphysiologic concentrations (23)(24)(25). More recent studies have found that CGRPα stimulates bone formation, although the physiologic relevance of these findings is unclear (26)(27)(28).…”
mentioning
confidence: 99%
“…28 In addition, the procalcitonin amino-terminal cleavage peptide stimulates U2OS cell proliferation. 31 However, the relationship of CT on osteoblast function is complex and may be bidirectional because CT receptor heterozygous knockout mice show an increase in bone formation.…”
mentioning
confidence: 99%